FAKTOR – FAKTOR YANG MEMPENGARUHI PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Hanastuti, Anisha Rahma; Srimindarti, Ceacilia (Dinamika Akuntansi Keuangan dan Perbankan, 2024)
The objective of this research is to analysis the influence of top management support and formalization of development of systems information on using accounting information systems. Population in this study are 46 of Hospitality Service Company in Semarang City. The respondents are the employee in Hospitality Service Company that work in accounting and finance department. The sampling method use convenience sampling methods. Data analysis that used for this research is structural test using SmartPLS. The result of this research found that top management support has positif effect on use of accounting information systems. However formalization of development of systems information has not effect on use of accounting information systems.